1998
DOI: 10.1615/critrevneurobiol.v12.i4.20
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Brain Angiotensin II Receptors

Abstract: Angiotensin II (ANG II) has been recognized recently as one of the stress hormones that participate in various stress-induced responses, including sympathetic (pressor, tachycardiac, and hyperthermic) and neuroendocrine responses. Brain ANG II receptors have been identified in many brain regions involved in the stress responses. During stress-exposure, ANG II increases in the plasma and in the brain. Central administration of ANG II induces stress responses, whereas central blockade of ANG II receptors results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…5,6 In particular, it has been shown that central or systemic administration of AT 1 receptor antagonists attenuated the increase in blood pressure and plasma catecholamine levels caused by several psycho-and physico-emotional stressors in rats and rabbits. 12,[24][25][26] Our data extend these findings by showing that targeted deletion of the AT 1A receptor gene selectively attenuates the pressor response to stress in mice.…”
Section: Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In particular, it has been shown that central or systemic administration of AT 1 receptor antagonists attenuated the increase in blood pressure and plasma catecholamine levels caused by several psycho-and physico-emotional stressors in rats and rabbits. 12,[24][25][26] Our data extend these findings by showing that targeted deletion of the AT 1A receptor gene selectively attenuates the pressor response to stress in mice.…”
Section: Stress Responsementioning
confidence: 99%
“…Recent pharmacological studies, however, indicate that the activation of angiotensin II type 1 (AT 1 ) receptors, and specifically those in the dorsomedial hypothalamus (DMH) and rostral ventrolateral medulla (RVLM), is required for full expression of sympathetic cardiovascular responses to various psychoemotional stressors in rats and rabbits. [3][4][5][6][7] Nonetheless, the effect of genetic deficiency of AT 1 receptors on cardiovascular reactivity to stress is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The change of ACTH and Cor adapt to the adverse environment, which is the evaluated index for the degree of stress and plays an extremely important role in the body (5). The weight of the organs change under the state of stress (6), including the pituitary, adrenal and hypothalamus. In the present study, by testing the organ coefficient of the pituitary and adrenal glands, and by testing the levels of ACTH and Cor in serum, whether the high temperature environment (32˚C) caused the heat-stress response in rats was explored.…”
Section: Introductionmentioning
confidence: 99%
“…Forebrain angiotensin II (ANG II) has been implicated in controlling cardiovascular and neuroendocrine responses to various psychological and physical stressors (42). In particular, blockade of AT 1 receptors in the anterior and paraventricular hypothalamic nuclei has been shown to attenuate increases in blood pressure and plasma catecholamines caused by immobilization stress in rats (18,21).…”
mentioning
confidence: 99%